Keragaman Rubus di Gunung Kembang Kabupaten Wonosobo Jawa Tengah dan Potensi Pemanfaatannya - Ratna Susandarini (Journal of Tropical Biodiversity and Biotechnology, 2016)
Rubus is a member of Rosaceae family where its natural habitat is in open areas of lowland and upland forests. Rubus has been reported found in Mount Kembang which is situated in Wonosobo, Central Java, but the number of species was unclear. The objective of this study was to investigate the Rubus diversity in M. Kembang and its uses by local people. Sample collecting was carried out using explorative methods on the slopes of M. Kembang. Uses information was obtained by interviewing the local people. The data were analyzed descriptively to provide species description along with their uses and potential in biological research. The result showed that there were four species of Rubus in M. Kembang, R. rosifolius J.E.Smith, R. chrysophyllus Reinw. Ex Miq., R. fraxinifolius Poir., and R. moluccanus L. with altitudinal distribution ranging from 945 m to 1,387 m above sea level. Among these four species R. rosifolius is the well-known one, that people sell the fruits in its fruiting season in the local market. Based on the literature some Rubus species in other areas in Java have potential as fresh fruits, source for making fruit jam, traditional herbal drink to cure diarrhoea and dysentery, or as ornamental plants. A few studies showed that the fruit extract of R. rosifolius has potential for natural dye in cosmetic products.